Physicochemical characteristics of selected palmyra Palm germplasm (Bangladesh Journal of Botany, 2026)
The palmyra palm (Borassus flabellifer L.) is a climate-resilient, low-maintenance crop with significant nutritional and commercial importance. This study evaluated the physicochemical properties of four locally available palmyra palm germplasm types -PP1 (blackish-yellow), PP2 (blackish-red), PP3 (light-black), and PP4 (deep-black) collected from Dumki Upazila, Patuakhali to identify the most promising variety. Significant (p ≤0.05) variation was observed among the germplasms in both physical and chemical attributes. PP1 recorded the highest fruit weight (1513.50 g), while PP2 exhibited superior juice yield (503.20 ml), pulp-to-peel ratio (7.28:1), total soluble solids (20.14%), total sugar (5.68%), titratable acidity (0.331%), carotene content (35.06 mg/100 g FW), and total phenolic content (9.28 mg GAE/g). In contrast, PP3 showed the lowest values in most parameters. The combination of high nutritional content and favorable processing attributes identifies PP2 as the most promising germplasm for both nutritional enhancement and commercial exploitation. These findings provide a scientific basis for selecting superior palmyra palm varieties to promote cultivation and value-added product development in Bangladesh.Bangladesh J. Bot. 55(2): 419-425, 2026 (June)